(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
We propose to analyze the ways in which affects are understood regarding the figure of violent emotion, particularly in a ruling of the Superior Court of Justice (Córdoba, 2014). Cecilia Macón states that, although affects are key to an analysis of power, they can be both transformative and conservative (2013). In this sense, we ask, what can the affective turn read in the letter of a ruling, in a possible legal precedent? How has emotion been understood there? More specifically, what makes an emotion plausible to excuse an action? The texts of law and jurisprudence are also sites through which emotions move, revealing material effects. In it, we intend to trace "the emotionality of texts in terms of the way in which they name or act certain emotions" (Ahmed, 2015, p.39). We will also reflect on the displacements that the figure in question has suffered, and its mitigating quality or not, based on the novelty of this particular ruling and its justification with contributions from feminist perspectives.